GLP-1 Receptor Agonists’ Impact on Fertility - A Review - Wojda, Joanna; Lesiczka-Fedoryj, Katarzyna; Walczak, Anna; Kościuszko, Zuzanna; Sobiński, Adam; Czerwonka, Matylda; Kurza, Katarzyna; Podolec, Julianna; Ciraolo, Silvia; Agnieszka Kulczycka-Rowicka (Quality in Sport, 2025)
Purpose of Research: The aim of the research is to summarize the impact of GLP-1 analogs on fertility according to clinical studies, particularly in obese or overweight women with PCOS. Research Materials and Methods: The study is built upon an analysis of current literature, clinical trials, meta-analyses, and systematic reviews as well as press reports from various sources. Data were collected from studies examining the effects of obesity on fertility, as well as the impact of GLP-1 analogs on both fertility and obesity. Basic Results: GLP-1 analogs promote weight management among obese and overweight patients leading to improvement in their fertility. Furthermore, they improve pregnancy rates in women with PCOS, although further examination is needed. Conclusions: We observe, GLP-1 analogs are often used in regulation of type 2 diabetes. They have proven their ability to impact a variety of hormonal as well as metabolic pathways. They manage glucose metabolism, appetite, as well as insulin secretion. Alongside their metabolic influence, research demonstrates that GLP-1 analogs may have an effect on the reproductive system, involving fertility via metabolic and hormonal pathways.